PENGARUH ATMOSFER DALAM GERAI, FASILITAS, DAN KEANEKARAGAMAN PRODUK TERHADAP MOTIF BELANJA HEDONIK PENGUNJUNG DI MAL GRESIK - Naning Ayu Astiwi (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2017)
This research is purposed to measure the partial and simultan of atmosphere influence in platform, facilities and all kinds of products to hedonic shopping motif of Gresik Mall visitors. This research takes 80 respondents from Gresik Mall visitors to research sample. Analysis results show that atmosphere in platform, facilities and all kinds of products influence in partial and simultan to hedonic shopping motif.